PLACE OF SPIRITUAL AND MORAL VALUES IN OUR SOCIETY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
The article highlights the relevance of the issue of preserving spiritual and moral values, customs and traditions, raising young people in the spirit of patriotism, being at the center of state policy, the important aspects of the reforms being carried out in this regard, and the traditional and modern methods of educating young people in the spirit of patriotism in the process of globalization.